Evaluating the effects of ICT core elements on CO₂ emissions: Recent evidence from OECD countries - Wolfgang Briglauer; Monika Köppl-Turyna; Wolfgang Schwarzbauer (EcoAustria - Institute for Economic Research, 2022)
Digitization-related services and applications are based on the information and communications technology (ICT) ecosystem and encompass almost all areas of society and economic sectors nowadays and exert numerous opposing effects in regard to electricity consumption and corresponding CO2 emissions. Our analysis aims to inform policy decision makers about the actual climate relevance of the ICT ecosystem by providing sound empirical evidence on the net effect of various ICT core elements based on recent OECD panel data utilizing panel econometric estimation methods that include instrumental variables. We found that the CO2-reducing positive indirect effects seem to outweigh the negative, in other words, CO2-increasing direct and indirect effects on average. Specifically, we found that, in addition to the lowering effect related to the use of basic broadband connections, there was another lowering effect-albeit smaller-related to new fiber-based broadband connections. In contrast, other elements of the ICT ecosystem, such as mobile broadband networks or electronic end-user devices, showed no significant net impact on CO2 emissions. Our main findings suggest that broadband networks can give rise to positive environmental effects for society. We conclude that undifferentiated climate policy measures imposed on the ICT ecosystem would not do justice to the identified heterogeneity, with numerous in part opposing effects, and likely would be accompanied by inefficiencies and market distortions.
Keywords: L52; L96; Q40; Q55; 330; ICT; digitization; CO2 emissions; electricity consumption; OECD data; panel econometrics